Reprogrammable ultra-fast shape-transformation of macroporous composite hydrogel sheets() - Guo, Hongyu (J Mater Chem B Mater Biol Med, 2017)
In this communication, we report a composite macroporous hydrogel sheet that can rapidly transform into multiple 3D shapes in response to near-infrared (NIR) light on demand. The transformation relies on the photo-thermal-induced asymmetric shrinking of the hydrogel material, which is further verified by finite element modeling.